ANALYSIS OF INVESTMENT ACTIVITY FORMATION PROCESSES IN SMALL BUSINESS SUBJECTS (Marketing Journal, 2025)
This article systematically analyzes the processes of formation of investment activity of small business entities, their role in economic stability, sources of financing and factors influencing the investment environment. Based on statistical data, the sources, growth rates and territorial distribution of investments in fixed capital are considered. The article provides practical recommendations for improving investment activity in the development of small businesses.
Keywords: small business; investment activity; fixed capital; economic growth; GDP; GNP